If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-5/5-2(y-59))=y-1/2
We move all terms to the left:
3y-5/5-2(y-59))-(y-1/2)=0
We add all the numbers together, and all the variables
3y-2(y-59))-(y-1/2-1)=0
We add all the numbers together, and all the variables
3y-2(y-59))-(y-1/2=0
We multiply all the terms by the denominator
3y*2-(2(y-59))-y*2-1=0
We calculate terms in parentheses: -(2(y-59)), so:Wy multiply elements
2(y-59)
We multiply parentheses
2y-118
Back to the equation:
-(2y-118)
6y-(2y-118)-2y-1=0
We get rid of parentheses
6y-2y-2y+118-1=0
We add all the numbers together, and all the variables
2y+117=0
We move all terms containing y to the left, all other terms to the right
2y=-117
y=-117/2
y=-58+1/2
| 5+10y+6=0 | | 7x2=-112 | | (5x-2)/(x+1)=0 | | -16+n=-18 | | -9.81=8.28b-6.16 | | 5(2x+5)=-6x+4x+5 | | 3x-2=3(10)-2= | | 4=2(j+1) | | 4=2(w+1) | | 2(w-3)-5=3 | | 2(w-3)-5=4 | | d+7/3=4 | | f-5/2=2 | | 5/6x-21/2=5/8x+33/8 | | c+14/3=0 | | -8=x+11(-2) | | 3z+7+10z=7+13z+10 | | 7(10-3)=5(15-4x) | | k+3/4=-3 | | 12=4(p-17) | | 6x-21=5x+12+x | | 4=v+11/4 | | -3b+3-2b=7+4b | | g+1/2=3 | | 3=v-1/2 | | 7|x−2|=4 | | F(x)=-31 | | 3(x-2)/3=21/3 | | 3/x-1/2=1 | | X-(x/10)=120000 | | 9+5y-7=0 | | (5x^2)+10x+4=0 |